Engineering mathematics Volume ll - Sharma, J.P (PHI Learning Private Ltd, 2011)
This Volume II of Engineering Mathematics is a sequel to volume I of Engineering Mathematics written by the same authors. It is designed for the second-semester courses for undergraduate students of engineering. It is a lucid and effective presentation of linear algebra, its mathematical concepts, its tools and techniques that are essential to the solution of problems encountered most frequently in connection with engineering applications. The book introduces students to the related concepts, rules and use of matrices and vector spaces in the solution of linear systems of equations which appear frequently as models of various engineering problems. Separate chapters are devoted to a thorough study of linear transformations, inner product spaces and eigenvalue problems in connection with matrices. The book makes liberal use of solved examples and provides plenty of exercises for homework in order that the students can apply these mathematical methods to the successful solution of real problems.